SISTEM PENGADUAN MASYARAKAT BERBASIS WEBISTE (SPM) - Muhammad Ilham Prayogi Ilham; Ita Puspita; Asa Hari Wibowo (Jurnal Informatika Ilmu Komputer dan Sistem Informasi, 2023)
The public complaint System implemented at Kendari City National Population and Family Planning Agency (BKKBN) office is currently still being carried out manually, namely by means of Short Message Service (SMS), letters, telephone and complaint boxes. With a manual complaint system will take a lot of time, effort, or money, so with this manual system the results obtained are less effective and efficient. Therefore, it is necessary to build an application that is able to provide a medium of communication between the public and officials at the Kendari city BKKBN office in informing complaints and grievances experienced by the community. In development this application the author uses the Laravel framework as a front-end, with the PHP programming language as a back-end, MySQL as database storage. The results of this study are the SPM Application, this application can help people make complaints to the BKKBN office anytime and anywhere as long as they are still connected to an internet connection.